Modulation of Sickle Red Blood Cell Adhesion and its Associated Changes in Biomarkers by Sulfated Nonanticoagulant Heparin Derivative. (April 2016) - Alshaiban, Abdulelah; Muralidharan-Chari, Vandhana; Nepo, Anne; Mousa, Shaker A.
Abnormal cellular adhesion is one of the primary causes of vaso-occlusive crisis in sickle cell disease (SCD). Levels of intercellular adhesion molecule 1 (ICAM-1) and P-selectin are upregulated, resulting in increased adhesion of leukocytes and sickle red blood cells (RBCs) to endothelium. This study compares the inhibitory effect of a sulfated nonanticoagulant heparin (S-NACH) derivative with a low-molecular-weight heparin, tinzaparin, on the adhesion of sickle RBCs to endothelium. The S-NACH exhibits minimum effects on hemostasis and bleeding and interferes with the binding of pancreatic cancer cells to endothelial cells via P-selectin. We show by static binding assay that pretreatment of both erythrocytes and endothelial cells with S-NACH significantly inhibits the increased adhesion of sickle RBCs to endothelial cells. The S-NACH treatment also decreases the higher plasma levels of (adhesion biomarkers) ICAM-1 and P-selectin in SCD mice. This investigation signals further research into the potential use of S-NACH in treating vaso-occlusions with minimal bleeding events in patients with SCD.